Anthropogenic activity and millennial climate variability affect Holocene mercury deposition of an alpine wetland near the largest mercury mine in China. (March 2023) - Peng, Haijun; Rong, Yimeng; Chen, Di; Sun, Ruiyang; Huang, Jie; Ding, Hanwei; Olid, Carolina; Yan, Haiyu
Abstract: Mercury (Hg) is a potentially toxic element that can be transported globally through the atmosphere, once deposited in the environment, has strong bioaccumulation and extreme toxicity in food webs, especially in wetland ecosystems. Anthropogenic Hg emissions have enhanced Hg deposition by 3–5 times since the industrial revolution, and the mining and smelting of Hg ore are important emission sources. However, the dynamics in Hg deposition around the largest Hg mine in China before the industrial revolution and their driving forces remain poorly explored. Here we reconstruct the atmospheric Hg depositional fluxes (named here Hg influx (Hginflux )) during the Holocene using a 450-cm alpine wetland sediment core taken from the Jiulongchi wetland, which is only 65 km to the Wanshan Mercury Mine. Our record shows an abrupt rapid increase in Hg concentration since 2500 cal yr BP, suggesting that Hg mining in southwest China may have started before the establishment of the Qin dynasty. Two major Hginflux peaks were found during the periods 10, 000–6000 and 6000 - 3800 cal yr BP, with an increase in Hg deposition by a factor of 4–8. These two peaks are also found in other terrestrial archives from several sites across the Northern Hemisphere. We speculate that critical millennial-scale climate changes, i.e., the Holocene Climatic Optimum (HCO) and the Mid-Holocene Transition (MHT), were the potential triggers of these two Hginflux peaks. This study highlights the importance of climatic variability and local Hg mining in controlling atmospheric Hg deposition during the Holocene. Graphical abstract: Image 1 Highlights: Hg mining activities in the Wanshan Hg Mine area might have started 2500 years ago. Pre-industrial Hg accumulation rate in Jiulongchi experienced 4–8 times variations. Two Hginflux peaks were detected in wetland archives across Northern Hemisphere. Intensified Hg accumulation in lake records was ascribed to millennial abrupt climatic changes.